(untitled) - Tubbs, Stewart L. (Boston, 2006)
Intended for the introductory communication concepts course, this text focuses on the principles and contexts of communication studies. The award-winning authors link theory and research with fundamental concepts and create plentiful opportunities for students to apply their understanding and develop useful communication skills. Their exposition is seasoned with intriguing case studies and stimulating examples drawn from contemporary life. In addition, Tubbs and Moss show a true sensitivity to diversity--a reflection of their professional interests in gender and cultural issues.
Keywords: Communication